Gereja Orang Basudara: The Contested Narrative From The Protestant Church of Moluccas - Lasatira, Frejhon Cleimen (DAS Institute, 2022)
This article describes the Gereja orang basudara concept in The Protestant Church of Maluku as the umbrella protecting and showing civic engagement, such as our strong tradition, religious institution, and mutual trust in Maluku. There are two essential points which are the history of Muslims-Christians' engagement in building social interaction and problem-solving after conflict by large, a sphere of solidarity. This research employed narrative research on the qualitative research method through historical and autoethnography approaches. The research result found that, first, the Gereja orang basudara term lives on the grassroots of society but did not show up in the institutional regime, which caused the failure of religious institutions and leaders to stop the violence during the social conflict in Maluku in 1999. After the battle, the Protestant Church of Moluccas practices peacebuilding by claiming their space and sphere as the room for all, where the church exists not only as a building for Christian people but also for Muslim people. Finally, the church does peacebuilding similar to peacebuilding in everyday life.